Antifungal activity of tyrosol and farnesol used in combination against Candida species in the planktonic state or forming biofilms - Monteiro, D. R. [UNESP]; Arias, L. S. [UNESP]; Fernandes, R. A. [UNESP]; Deszo da Silva, L. F.; de Castilho, M. O.V.F.; da Rosa, T. O.; Vieira, A. P.M. [UNESP]; Straioto, F. G.; Barbosa, D. B. [UNESP]; Delbem, A. C.B. [UNESP] (Oxford University Press (OUP), 2017)
Aim: This study examined the antifungal activity of the combination of tyrosol and farnesol against Candida albicans and Candida glabrata in the planktonic state or forming biofilms. Methods and Results: The effect of drug association against Candida planktonic cells was assessed by the fractional inhibitory concentration index. Mono- and dual-species biofilms were developed during 24 h and then treated with the compounds for 3 days, with two daily treatments of 1 min each. After, the total biomass, metabolic activity and the number of cultivable cells were quantified. Planktonic cells of the two species showed a similar susceptibility to the drug combination, however, a synergistic effect was only verified for C. glabrata. Regarding biofilm susceptibility, significant reductions in C. glabrata biomass, metabolism of C. albicans and mixed biofilms, and cultivable cells of single biofilms were verified for the drug combination, indicating an additive effect. For all other experiments, the effects were classified as indifferent. Conclusion: The combined use of tyrosol and farnesol was advantageous for some of the analysed parameters against Candida species. Significance and Impact of the Study: These findings may contribute to the development of oral care products containing tyrosol and farnesol to combat oral infections caused by Candida species.
Keywords: antimicrobials; biofilms; fungi; mycology; quorum sensing